Experimental Study on Erosion of String Inner Wall in Perforation Interval in Liquid-Solid Two-Phase Flow. Issue 1 (1st March 2022) - Zhang, Kui; Wang, Junchao; Yuan, Liang; Mu, Lingyu; Cheng, Jiarui; Wei, Wenlan
Abstract: In the process of large displacement fracture injection, high flow velocity sand-carrying fluid causes serious erosion corrosion to the borehole. Based on the high-speed liquid-solid two-phase erosion experiments, the erosion experiments of single-hole set with flow velocity, sand concentration and grain size, and the three-dimensional profile scanning of the eroded orifice were carried out to investigate the erosion and corrosion expansion law of the high-speed jet orifice. The study shows that the erosion rate increases with the increase of discharge volume, sand concentration and particle size, and the change of discharge volume and sand concentration has the most significant effect on the erosion of the hole. The prediction of the hole expansion law of single hole with sand liquid injection shows that the hole diameter expands to 13mm-19mm after 90min of construction of 8 clusters of 24 holes, while the hole diameter expands to 11.7mm-12.8mm after 90min of construction of 3 clusters of 48 holes. 3 clusters of 48 holes have smaller hole diameter after the same construction time, which is better than 8 clusters of 24 densely packed holes.